Learning assistance for students with special needs at SLB Kirana Hati Bunda, Tamiajeng Village, Trawas District - Inggit Marodiyah; Natasya Dwi Puspitasari; Dhita Anggraeni; Risa’ida Dwi Mufidah; Layyinatus Saniyyah; Yusrilda Maharani (Community Empowerment, 2024)
The purpose of this community service is to help provide learning assistance to students at SLB Kirana Hati Bunda Tamiajeng Village. The service activities carried out at Kirana Hati Bunda SLB use a hands-on method. This activity was carried out well and smoothly. With this service activity, it provides a more enjoyable and effective learning experience and can provide additional support for students.